Policy Recommendations for Chagas Disease: An Emerging Concern of Public Health Significance for the U.S. Military - Gerardo J. Pacheco; Jose A. Betancourt; Diane Dolezel; Bradley M. Beauvais; Joseph E. Marcus; Paul Lenhart; Paula S. Granados (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Chagas disease, caused by Trypanosoma cruzi , poses an emerging and under recognized threat to U.S. military personnel deployed in endemic regions. Despite significant morbidity and mortality risks, the US Department of Defense (DoD) lacks comprehensive policies for Chagas disease prevention, screening, or treatment, unlike other similar infectious diseases. We conducted a comparative policy analysis of existing DoD policies on tuberculosis, HIV, and hepatitis C to inform the development of Chagas disease policy. Using an adapted Political, Administrative, Social, Technological, Economic, Legal factors (PASTEL) framework, we evaluated five policy alternatives through expert consensus scoring. Military health policies and literature were systematically reviewed to identify screening protocols, risk assessment tools, and prevention strategies. Analysis of current military screening policies revealed significant gaps in Chagas disease coverage in comparison with analogous infectious diseases. The decision matrix analysis identified an integrated Periodic Health Assessment (PHA) approach as the optimal policy alternative (weighted score 4.20/5.0), followed by targeted risk-based screening (3.85/5.0). Universal screening scored lowest (2.20/5.0) due to poor cost-effectiveness and implementation challenges. The recommended approach leverages existing annual health assessment infrastructure while incorporating Chagas disease-specific risk evaluation tools. A tiered policy strategy integrating Chagas disease risk assessment into routine military health evaluations offers the most feasible approach for protecting service members. Implementation should prioritize risk-based screening, vector-control measures (e.g., insecticide-treated uniforms), and enhanced surveillance in endemic deployment areas. This framework provides an evidence-based foundation for developing comprehensive DoD Chagas disease policies.